The impact of current peri-operative care on outcomes for patients with hip fracture - Marufu, Takawira Chrispen (2017)
Background: Fragility hip fractures among the elderly constitute a significant global public health problem. The disease is devastating for both patient and the family, often resulting in reduced mobility (disabling), increased reliance on others, diminished health and quality of life, and sometimes death. Thirty-day and one-year mortality rates are high. Postoperative morbidity and ‘delayed discharges’ are frequently cited with an average length of hospital stay of 19.5 days.